Selective non-catalytic reduction – Fe-based additive hybrid technology. (15th November 2017) - Daood, Syed Sheraz; Yelland, Thomas S.; Nimmo, William
Highlights: A Fe-based additive altered performance of selective non-catalytic reduction. Pseudo-catalytic activity provides active sites for ammonia to reduce NO. This interaction led to greater NO reduction and greater ammonia utilisation. This is an economically viable opportunity for full-scale coal combustion plants. Abstract: Fe-based additives can be used to improve coal combustion and reduce NOx emissions; further to this, iron oxide (Fe2 O3 ) has been found to interact with ammonia. Therefore, it is critically imperative to understand and assess the impact of the Fe-based additive on the use of ammonia based selective non-catalytic reduction (SNCR) and to evaluate the economic feasibility of such a combination for full-scale use. Experiments were performed using a 100 kWth down fired-combustion test facility burning pulverised coal over three Fe-based additive concentrations, while the ammonia input was varied between normalised stoichiometric ratios 0–3. This study finds evidence of an interaction between the Fe-based additive and SNCR. The interaction leads to greater ammonia utilisation and an increased NOx reduction due to the SNCR of >10%. The interaction is theorised to be pseudo-catalytic with the fuel additive providing an active site for ammonia to reduce NO. Using Carnegie Mellon University's 'Integrated Environmental Control Model' (IECM), this has been shown to create an economically viable opportunity to increase SNCR effectiveness.